2008
DOI: 10.4049/jimmunol.180.10.6553
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a TGF-β-Specific Multistep Gene Expression Program in Mature Macrophages Requires Glucocorticoid-Mediated Surface Expression of TGF-β Receptor II

Abstract: Alternatively activated (M2) macrophages regulate steady state-, cancer-, and inflammation-related tissue remodeling. They are induced by Th2-cytokines and glucocorticoids (GC). The responsiveness of mature macrophages to TGF-β, a cytokine involved in inflammation, cancer, and atherosclerosis, is currently controversial. Recently, we demonstrated that IL-17 receptor B is up-regulated in human monocyte-derived macrophages differentiated in the presence of Th2 cytokines IL-4 and TGF-β1. In this study, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 67 publications
0
78
1
4
Order By: Relevance
“…For example, macrophages differentiated in the presence of the glucocorticoid dexamethasone exhibit increased sensitivity to TGF-b resulting from an increase in TGF-b receptor expression and induced lipid uptake (76). However, the relative contributions of these numerous factors to macrophage polarization, as well as the complex and synergistic interactions between the factors, are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, macrophages differentiated in the presence of the glucocorticoid dexamethasone exhibit increased sensitivity to TGF-b resulting from an increase in TGF-b receptor expression and induced lipid uptake (76). However, the relative contributions of these numerous factors to macrophage polarization, as well as the complex and synergistic interactions between the factors, are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Strong arguments in favor of therapeutic targeting of macrophages is provided by recent findings made by us and others demonstrating high levels of macrophage functional plasticity (5,8,9). It was demonstrated that every combination of cytokines, hormone growth factors, or even nutritional conditions leads to the development of a specific macrophage phenotype (10)(11)(12). Highly specific effects on macrophages are demonstrated for cytokines like IFN-g, various ILs, CC-chemokines, glucocorticoids, retinoids, and increased glucose concentration in culture medium (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…For example, TGF-b inhibits LPS-induced and proinflammatory cytokineinduced expression of a number of macrophage activation markers (e.g., matrix metalloproteinase-12 -12, inducible NO synthase, TNF) in a Smad-dependent manner (27)(28)(29)(30). The knowledge of the signaling that is induced by TGF-b in macrophages is, however, limited to the activation of the canonical Smad2/3-mediated pathway (12,31).…”
mentioning
confidence: 99%
“…Smad7 regulation the TGF-β/ Smads pathway may not the major molecular mechanisms of participate in regulating cholangiocarcinoma EMT.On the other hand,with the development of the EMT process. Smad7 positive expressing rate was higher, which may be a negative feedback regulation of the body response to TGF-β1-induced tumor invasion and metastasis (Park et al, 2004;Gratchev et al, 2008).…”
Section: Discussionmentioning
confidence: 99%